Living Islam in Action: Embodied Volunteerism, Transformative Learning, and Muzakkī Social Agency in Indonesia - Dwi Retno Damayanti; Rizqi Handayani; Amy Maulana; Mohamad Ardin Suwandi (Graduate School of UIN Syarif Hidayatullah Jakarta, 2026)
This study examines how Islamic volunteerism functions as a process of transformation within the context of Islamic philanthropy in Indonesia. Moving beyond dominant perspectives that emphasize motivation and well-being, this research positions volunteer engagement as an embodied transformative learning process. The research aims to analyze how service experiences shape muzakkī who participate as volunteers in the (Badan Amil Zakat Nasional) BAZNAS Volunteer program understanding and practice of Islam. Employing a qualitative case study design, the research was conducted within the BAZNAS Volunteer activity at Kampung Muallaf Cepak Buah, Lebak, Banten, from 30 November to 1 December 2024, involving 15 participants purposively selected from 41 volunteers. Data were collected through semi-structured interviews, participant observation, and document analysis, and analyze using an integrative framework combining Transformative Service Research (TSR), Transformative Learning Theory (TLT), and the concept of self-embodiment. The findings show that encounters with social inequality foster religious reflexivity, reshape meaning, and transform Islamic values into lived and enacted practices. The study highlights self-embodiment as a key mechanism bridging service experience and emerging transformative learning. This research contributes to the development of Islamic studies by demonstrating that Islamic philanthropy serves as a dynamic space for the transformation of living Islam, and offers practical insights for designing volunteer programs that foster deeper religious engagement and sustained social commitment.